Astragalus polysaccharides enhance the immune response to avian infectious bronchitis virus vaccination in chickens. (October 2017) - Zhang, Pengju; Wang, Jun; Wang, Weixia; Liu, Xiaohui; Liu, Haiyan; Li, Xintao; Wu, Xinghong
Abstract: Astragalus polysaccharides (APS) are biological macromolecules extracted from Astragalu s species that have strong immunoregulatory properties. In this study, APS were employed as an adjuvant for an avian infectious bronchitis virus (IBV) vaccine, and its effects on the cellular immune and humoral immune responses to vaccination in chicken were investigated. One hundred and fifty chicken were randomly divided into five groups (n = 30, each group). The chickens in all groups, except for the unvaccinated control group, were vaccinated with an IBV DNA vaccine. Three of the four vaccinated groups were administered different doses of APS (APSL, 10 mg/kg; APSM, 50 mg/kg; and APSH, 100 mg/kg) after the first vaccination, and the remaining vaccinated group served as a control, without any additional treatment. At 14, 28, and 42 days after the first vaccination, serum anti-IBV antibody titers; peripheral lymphocyte proliferation; and the mRNA expression of IL-1β, IL-2, IL-8, and TNF-α in the spleen were assessed by enzyme-linked immunosorbent assay (ELISA), the cell counting kit-8 (CCK-8), and real time quantitative RT-PCR (qRT-PCR), respectively. At most time points, the titer of IBV-specific antibodies, lymphocyte proliferation, and IL-1β, IL-2, IL-8, and TNF-α mRNA expression levels were higher in three APS groups than in the vaccine control group, and these increases were dose-dependent. These data suggest that APS could be used as an adjuvant for IBV vaccination to provide better protection against IBV infection. Highlights: Oral supplementation with APS at dos 50 mg/kg and 100 mg/kg can elevate the specific antibody titers to the IBV DNA vaccine. APS could increase IBV DNA vaccine cell-mediated immunity by promoting lymphocyte proliferation and increasing cytokine production. APS could be used as an adjuvant for IBV vaccination to provide better protection against IBV infection.